Peningkatan Keterampilan Menulis Surat Pribadi Dalam Bahasa Inggris Dengan Menggunakan Padlet Pada Siswa Kelas XII TKJ SMKN 3 Tabanan Tahun Pelajaran 2021/2022 - I Wayan, Mertayasa (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2023)
This classroom action research was carried out in Class XII TKJ 1 SMKN 3 Tabanan with a total of 23 students. The objectives to be achieved in this study are to improve students' ability to compose personal letter texts, develop distance learning strategies and online learning models that are effective, efficient and fun. Students can involve themselves actively in communication activities by expressing their ideas, opinions and feelings. simply either orally or in writing online. The technique used in this study was to make observations/observations and give student performance tests in the form of online written tests. Using the Padlet application as a means for sending personal letters can improve the abilities of class XII TKJ 1 SMKN 3 Tabanan students for the 2021/2022 academic year. This can be proven through written evaluations/tests with the average student score in the first cycle being 57, 17 increasing in the third cycle to 70.43. Online learning or distance learning is currently carried out synchronously or asynchronously. Using interesting media is proven to increase student activity. In cycle I there were 9 students who successfully participated in the Zoom Meeting activity. 12 people in cycle II and 17 people in cycle III. Of these, 6 students were unable to use communication tools.